Analytical modelling approach for switched reluctance machines with deep saturation - Ding, Xiaofeng; Rashed, Mohamed; Hill, Christopher Ian; Bozhko, Serhiy (2016)
This paper presents an analytical modelling approach for Switched Reluctance Machines (SRMs) with a wide saturation range. There are many existing analytical modelling approaches in literature that give good accuracy, however most do not consider modelling accuracy in the deeply saturated region of operation. The proposed modelling method is suitable for SRMs operating under the entire saturation range. The proposed methodology begins by modelling the inductance profile as a Fourier series in order to take advantage of its approximately sinusoidal variation with respect to rotor position. Improvements are then presented to achieve higher accuracy. Flux linkage and torque models for the SRM can then be derived from the inductance model. An example 60kW 6/4 SRM with a wide saturation operating range is used for analytical modelling. It is shown that high accuracy is obtained by the derived analytical model when evaluated against the measured magnetic characteristics of the machine.